Color Distortion of Digital Image and its Detection - Xia Yanhui; Wang Zhengyou; Wang Wan; Wang Jin; Wan Zheng (Institute of Advanced Engineering and Science, 2013)
To solve the problem of color distortion in the communication and reproduction process, the paper firstly analyzes the causes of the color distortion phenomenon. Then, the paper proposes the corresponding image color distortion detection algorithm based on the HSI color model. In the proposed method, the color image is transformed from RGB space to HSI space firstly; in HSI space, the reference image and the distortion image’s hue differences and saturation differences are calculated. Experimental results on LIVE images show that the measured results of the model with subjective scoring after the nonlinear fit the correlation coefficient up to 0.95.DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3080